Study of effect of finite element mesh distortion in free vibration and geometric nonlinear analyses using 2D finite elements - Yu, Modi (Nanyang Technological University, 2020)
When performing analysis using Finite Element Methods (FEM), mesh distortion is a common problem that cannot be avoided. Mesh distortion usually happens when an object with a complex shape is being modelled and causes the results obtained to deviate from its exact solutions. To circumvent this issue, one usually has to either re-mesh the model or refine the current mesh, both resulting in additional costs incurred. Hence, the study of mesh distortion has been of interest to researchers, especially since FEM is getting more popular across various engineering fields. Although several research has been done on the effect of mesh distortion on classical isoparametric elements, none was done on the popular Ansys PLANE183 element that is widely used commercially. Hence, this project attempts to study the effect of mesh distortion on the Ansys PLANE183 element. Through two test problems formulated, the behaviour of the element with mesh distortion introduced under free vibration analysis and nonlinear analysis are analysed and discussed in this report.